Fabrication of pes/f-mwcnt/licl membrane and separation of nannochloropsis sp - Idris, Ani (2014)
Background: Nannochloropsis sp. is one of the promising candidate for biofuel production. The membrane application in separating the Nannochloropsis sp. is referring to microalgae harvesting in the conventional biofuel production. Objective: The purpose of this modification is to develop an efficient membrane for separating Nannochloropsis sp from water solution Results: It was found that the membrane morphology, pore size, hydrophlicity and permeation rate were influenced by the quantity of LiCl inside the membrane. Morover, larger membrane pore size and porosity have help in high separation rate of Nannochloropsis sp. despite of flux loss. Conclusion: As conclusion, all PES modified membranes were able to separate 100% of Nannochloropsis sp. from the water solution.